A review on nanostructures of high-temperature thermoelectric materials for waste heat recovery. (October 2016) - Fitriani,; Ovik, R.; Long, B.D.; Barma, M.C.; Riaz, M.; Sabri, M.F.M.; Said, S.M.; Saidur, R.
Abstract: Alternative renewable energy sources are immensely important in view of the increase in worldwide energy needs and environmental effects. The thermoelectric (TE) technology is being seen as the perfect solution for both issues due to its ability to convert heat directly into electricity without CO2 emission. However, the application of TE materials for commercial devices is still limited due to their low conversion efficiency of 10–15%. Currently the improvement of TE efficiency is challenging due to the relationship among physical properties, i.e., electrical conductivity, thermal conductivity and Seebeck coefficient which often counter each other and are restricted by the carrier concentrations. Fortunately, nanostructures have been shown to be able to disconnect the link among these physical properties to enhance the conversion efficiency of materials. Thus, the purpose of this review paper is to present the different nanostructured approaches for enhancing the TE properties of materials. The various techniques have been widely used to synthesize the bulk nanostructure and low dimensional systems were also described. A discussion on potential heat resources for the TE conversion, as well as the recent progress in TE is provided in terms of material, process and technology. Nanostructured skutterudites, half - Heusler, oxides and Si-Ge binary system were focused in this review paper due to the fact that the TE materials are among the best candidates for high-temperature applications. We also included our estimation in output electrical power of thermoelectric generation (TEG) for these type TE materials. Besides that, some innovations for the development of TE materials were mentioned. In addition, we also discussed the estimation of the TE cost to shed some light on commercializing considerations. We concluded that the high cost of the heat exchanger and ceramic substrate system components proved to be barriers in reducing the cost of TEG.